The “lost treasure” of Brazilian transitional justice: the CNV, university commissions and the work of historians (Tempo e Argumento, 2021)
The article aims to present and analyze the author’s experience as coordinator of the work of the National Truth Commission with the university commissions. It also seeks to reflect on the social role of the historian and the ethical challenges involved, and to show the importance of the participation of historians in the processes of transitional justice beyond the construction of a historical memory and the opening of new collections on the dictatorial past.